Photoinduced polarization enhancement on biased bilayer graphene in the Landau level regime - López, Alexander; Berche, Bertrand; Schliemann, John; Mireles, Francisco; Santos, Benjamin (Journal of physics. Condensed matter, 2019)
We investigate the charge carrier dynamics in bilayer graphene subject to monochromatic laser irradiation within the Landau level quantization regime. Even though the radiation field does not lift the energy degeneracy of the lowest Landau levels (LLs), it nevertheless has a strong effect on the photoinduced pseudospin polarization response for higher LLs (). Our results show that the photoinduced bandgaps lead to a finite response of the averaged pseudospin polarization with nontrivial oscillating behavior. It is shown that the contribution from these higher LL transitions turns out to be crucial to achieve an enhanced photoinduced polarization in radiated bilayer graphene. The experimental feasibility of our findings is also discussed.